FUNDAMENTALITY OF SCIENTIFIC AND TECHNICAL KNOWLEDGE IN TECHNICAL UNIVERSITIES IN INFORMATION SOCIETY - Ченбай, Н. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The strategies of raising the level of the fundamentality of scientific knowledge in the technical universities are defined.